ANALISIS PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN MEMILIH PROGRAM STUDI (Studi pada Jurusan Akuntansi dan Jurusan Administrasi Bisnis di Politeknik Negeri Banjarmasin) - Agus Irawan; Ikhwan Faisal (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
The decision to continue their study to university level is an ideal choice for senior high or vocational school graduates. University is an educational institution that is expected to create human resources who have added values and who are able to make scientific works and innovations in technology. The objective of this research is to analyze simultaneous, partial, and dominant influence of Marketing Mix for Service which consists of product, price, promotion, place, people, process, and physical evidence (7Ps) toward the decision to choose study major at the State Polytechnic of Banjarmasin (Accounting Program and Business Administration Program). This study is aimed to test different decisions in choosing one of the four majors offered. The population in this study is all 854 students of Accounting and Business Administration Programs of the State Polytechnic of Banjarmasin. The sampling technique used in this study is Proportionate Stratified Random Sampling with total 100 samples taken. The hypothesis of the study is tested by using multiple linear regression analysis and one way analysis of variance (one way anova). The first finding of the study is that in terms of simultaneous influence, Marketing Mix for Service consisting of product, price, promotion, place, people, process, and physical evidence has a significant influence toward the decision to choose major of study. The second finding is that in terms of partial influence, only variables of product, price, promotion, and place that have significant influence while other variables (people, process, and physical evidence) do not have significant influence toward the decision to choose major of study. The third finding is that variable of price has the most dominant influence toward the decision. The last finding of the research is there is no significant average variance on choosing one of the majors of Accounting, ALKS, Business Administration, and Information Management Programs of the State Polytechnic of Banjarmasin